Anterior Spinal Artery Syndrome: Reversible Paraplegia after Minimally Invasive Spine Surgery - J. Bredow; J. Oppermann; K. Keller; F. Beyer; C. K. Boese; K. Zarghooni; R. Sobottke; P. Eysel; J. Siewe (Case Reports in Orthopedics)
Background Context. Percutaneous balloon kyphoplasty is an established minimally invasive technique to treat painful vertebral compression fractures, especially in the context of osteoporosis with a minor complication rate. Purpose. To describe the heparin anticoagulation treatment of paraplegia following balloon kyphoplasty. Study Design. We report the first case of an anterior spinal artery syndrome with a postoperative reversible paraplegia following a minimally invasive spine surgery (balloon kyphoplasty) without cement leakage. Methods. A 75-year-old female patient underwent balloon kyphoplasty for a fresh fracture of the first vertebra. Results. Postoperatively, the patient developed an acute anterior spinal artery syndrome with motor paraplegia of the lower extremities as well as loss of pain and temperature sensation with retained proprioception and vibratory sensation. Complete recovery occurred six hours after bolus therapy with 15.000 IU low-molecular heparin. Conclusion. Spine surgeons should consider vascular complications in patients with incomplete spinal cord syndromes after balloon kyphoplasty, not only after more invasive spine surgery. High-dose low-molecular heparin might help to reperfuse the Adamkiewicz artery.